Simulasi Kopling Magnetik Transfer Energi Nirkabel (Wireless Power Transfer) - Affan Bachri; Zainal Abidin (Universitas Islam Lamongan, 2020)
One method for energy transfer wireless is magnetic induction couplings. In general, copper is the most important element in producing magnetic flux in the form of coils or coils. Copper is used as an electrical transfer media because the material consists of many electrons that can move freely. Magnetic coupling simulation with Multisim 12.00 shows that the transmitter coil induces a receiver coil and energy transfer occurs.